Educating First-Grade Elementary Students to Soap Handwashing to Enhance COVID-19 Readiness during the New Normal Era: Edukasi Mencuci Tangan Sabun bagi Siswa SD Kelas 1: Tingkatkan Kesiapsiagaan COVID-19 Era New Normal - Hakim Zulkarnain; Candra Panji Asmoro; Purwaningsih Purwaningsih; Andri Setiya Wahyudi; Wahyuni Tri Lestari (KHD Production, 2024)
The age group of children is at risk of contracting and transmitting COVID-19, so education is needed to build preparedness on the importance of washing hands to prevent transmission of COVID-19 in the new normal era. The purpose of community service is to improve the preparedness of school students. Community service was carried out on June 16, 2021, to 27 students of elementary school X aged 6-7 years. Information is conveyed through short stories for kids. Hand washing movements are conveyed through videos and hand washing songs so that children become more interested and easier to follow. The materials presented included the prevention of COVID-19 in the new normal era, an explanation of hand washing with soap according to the Ministry of Health standards as a form of preventing COVID-19 transmission, and video playback of the 6-step handwashing movement. Post education was found that 95% students (38 of 40) level of knowledge was high which proven by the ability to recall all the steps of soap handwashing. The children's knowledge about washing hands using soap to prevent COVID-19 is increasing, and children are able to wash their hands in the right steps according to Ministry of Health standards. Education for school-age children requires the right method so that children want to participate in education comfortably.